Comparison Between RIPASA And Modified Alvarado Scoring System For Diagnosis of Acute Appendicitis - Devanathan, Suhas; Akther, Jawed (International Journal of Psychosocial Rehabilitation, 2020)
Background: Amongst the surgical emergencies, acute appendicitis is most common. Present study will compare RIPASA and Modified Alvarado Scoring System to find out more relevant and better applicable system of scoring in order to aid prior diagnosing of acute appendicitis.Objectives; To assess the RIPASA scoring system and Modified Alvarado Scoring System for the diagnosis of acute appendicitis, and compare them with various parameters. Methodology Study will be conducted in the department of general surgery in Acharya Vinoba Bhave Rural Hospital Sawangi, Wardha. Results There is high specificity and sensitivity amongst the scoring systems and also a high diagnostic accuracy in diagnosing acute appendicitis. Conclusion: These systems of scoring help improve the accuracy of diagnosis and sequential reduction of unnecessary removal of appendix and thus the negative impacts of surgery. Keywords: appendicitis, RIPASA scoring system, modified ALVARADO scoring system,